2020
DOI: 10.1042/bsr20193156
|View full text |Cite
|
Sign up to set email alerts
|

Clozapine protects adult neural stem cells from ketamine-induced cell death in correlation with decreased apoptosis and autophagy

Abstract: Adult neurogenesis, the production of newborn neurons from neural stem cells (NSCs) has been suggested to be decreased in patients with schizophrenia. A similar finding was observed in an animal model of schizophrenia, as indicated by decreased bromodeoxyuridine (BrdU) labelling cells in response to a non-competitive N-methyl-d-aspartate (NMDA) receptor antagonist. The antipsychotic drug clozapine was shown to counteract the observed decrease in BrdU-labelled cells in hippocampal dentate gyrus (DG). However, p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(23 citation statements)
references
References 76 publications
0
23
0
Order By: Relevance
“…Promisingly, one study has shown the potential of ketamine to counteract its own neurotoxic effects by inducing the production of the activity-dependent neuroprotective protein (ADNP); pretreatment with a subanesthetic dose of ketamine before sedation might upregulate the production of this protein and provide a neuroprotective effect in rats [151]. Other approaches to mitigating the risk of ketamine-induced neuronal apoptosis are being investigated; for example, clozapine has been shown to improve the viability of mouse neuronal stem cells that are exposed to ketamine [156].…”
Section: Neurologic Applications Of Ketaminementioning
confidence: 99%
“…Promisingly, one study has shown the potential of ketamine to counteract its own neurotoxic effects by inducing the production of the activity-dependent neuroprotective protein (ADNP); pretreatment with a subanesthetic dose of ketamine before sedation might upregulate the production of this protein and provide a neuroprotective effect in rats [151]. Other approaches to mitigating the risk of ketamine-induced neuronal apoptosis are being investigated; for example, clozapine has been shown to improve the viability of mouse neuronal stem cells that are exposed to ketamine [156].…”
Section: Neurologic Applications Of Ketaminementioning
confidence: 99%
“…For this reason, the authors concluded that clozapine does not have protective properties against newly formed nerve cells [18]. An anti-apoptotic effect of clozapine was also observed [19]. Another atypical antipsychotic olanzapine, supports adult neurogenesis mainly within the SVZ, although there are some reports that also suggest this effect occurs in the SGZ [1].…”
Section: Resultsmentioning
confidence: 99%
“…Autophagy has attracted increasing attention in relation to brain disorders; it is a housekeeping process that maintains cellular homeostasis and can be activated by multiple factors, including exposure to stress [78]. In vitro studies also identified changes in the autophagy pathway following exposure to ketamine [77,79,80]. This indicates that ketamine anesthesia triggered autophagy in the hippocampus of the fetus and in PC12 cells [77].…”
Section: Neurochemical Cascades and Other Mechanismsmentioning
confidence: 95%